Association of Multimorbidity with Mortality and Healthcare Utilization in Chronic Kidney Disease. Issue 4 (23rd November 2016) - Bowling, C. Barrett; Plantinga, Laura; Phillips, Lawrence S.; McClellan, William; Echt, Katharina; Chumbler, Neale; McGwin, Gerald; Vandenberg, Ann; Allman, Richard M.; Johnson, Theodore M.
Abstract : Objectives: Chronic kidney disease (CKD) almost universally occurs in individuals with other medical problems. However, few studies have described CKD‐related multimorbidity using a framework that identifies chronic conditions as concordant (having overlap in treatment goals) versus discordant (having opposing treatment recommendations) and unrelated (having no overlap, but contributing to complexity via different resource requirements). Design: Retrospective cohort. Setting: Veterans Affairs (VA) Medical Centers. Participants: VA patients (n = 821, 334) ages 18–100 years with at least one outpatient visit and incident CKD defined as an estimated glomerular filtration rate <60 mL/min/1.73 m 2 for at least 3 months between January 1, 2005 and December 31, 2008 after excluding prevalent CKD. Measurements: We determined the associations of number of chronic conditions (1, 2, 3, 4, 5, 6 or more) stratified by the presence of one or more discordant/unrelated conditions with mortality, hospitalizations and emergency department (ED) visits. Results: There were 381, 187 deaths over 6.8 median years of follow‐up. Higher risks of death, hospitalization and ED visits were associated with higher number of chronic conditions, among those with and without discordant/unrelated conditions. However, the magnitudes of the associations were consistently larger when at least one discordant/unrelated condition was present. For example, compared to patients with one concordant condition, patients with six or more concordant conditions had an age‐, race‐ and sex‐adjusted hazard ratio (HR) for mortality of 1.72 (95% CI 1.64–1.80) whereas those with six or more conditions, at least one of which was discordant/unrelated, had a HR of 2.05 (2.01–2.09) ( P ‐interaction <0.001). Conclusions: The presence of one or more discordant/unrelated conditions was associated with increased risk for adverse health outcomes, beyond the effect of multimorbidity.